Physiological and microbial adjustments to diet quality permit facultative herbivory in an omnivorous lizard - Kohl, Kevin (2016)
While herbivory is a common feeding strategy in a number of vertebrate classes, less than 4% of squamate reptiles feed primarily on plant material. It has been hypothesized that physiological or microbial limitations may constrain the evolution of herbivory in lizards. Herbivorous lizards exhibit adaptations in digestive morphology and function that allow them to better assimilate plant material. However, it is unknown whether these traits are fixed or perhaps phenotypically flexible as a result of diet. Here, we maintained a naturally omnivorous lizard, Liolaemus ruibali, on a mixed diet of 50% insects and 50% plant material, or a plant-rich diet of 90% plant material. We compared parameters of digestive performance, gut morphology and function, and gut microbial community structure between the two groups. We found that lizards fed the plant-rich diet maintained nitrogen balance and exhibited low minimum nitrogen requirements. Additionally, lizards fed the plantrich diet exhibited significantly longer small intestines and larger hindguts, demonstrating that gut morphology is phenotypically flexible. Lizards fed the plant-rich diet harbored small intestinal communities that were more diverse and enriched in Melainabacteria and Oscillospira compared with mixed diet-fed lizards. Additionally, the relative abundance of sulfate-reducing bacteria in the small intestine significantly correlated with whole-animal fiber digestibility. Thus, we suggest that physiological and microbial limitations do not sensu stricto constrain the evolution of herbivory in lizards. Rather, ecological context and fitness consequences may be more important in driving the evolution of this feeding strategy.